Wage Compression within the Firm - Marco Leonardi; Michele Pellizzari; Domenico Tabasso (Institute for the Study of Labor (IZA), 2015)
We study the distributional effect of a wage indexation mechanism - the Scala Mobile (SM) - that heavily compressed the distribution of Italian wages during the 1970s and 1980s. The SM imposed large real wage increases at the bottom of the distribution and was essentially irrelevant for high-wage workers. We document that this mechanism triggered a strong redistribution within the firm. Skilled workers received lower wage adjustments when employed at firms with many unskilled workers and they tended to move towards more skill-intensive firms. We rationalize these findings with a simplified model of intra-firm bargaining with on-the- job search.
Keywords: J01; J31; J50; 330; labor market institutions; wage indexation; inequality; intra-firm bargaining